Profil Pasien Morbus Hansen di Poliklinik Kulit dan Kelamin Rspal dr. Ramelan Periode 2016–2021 - Putu Wahyu Mahaputra; Putu Pradika Apriano; Putu Sri Ayu Yulian Dianawati; R. Gery Susianggara Purnama Adi; Raditya Manusakti; Renata Prameswari; Olivia Mahardani Adam (Universitas Pahlawan Tuanku Tambusai, 2023)
Morbus Hansen is an infectious skin disease caused by Mycobacterium Leprosy which besomes one of the neglected disease and very common in Indonesia and other subtropical countries. World Health Organization (WHO) reported the number of new cases of Hansen's disease on 2018 in 159 countries was 208,619 cases. Indonesia ranks third in the world with a total of 17,017 cases, after India and Brazil. On this retrospective descriptive study regarding the profile of Morbus Hansen patients at the Dernatovenerology Clinic, dr. Ramelan Hospital on 2016–2021, there were 24 Morbus Hansen patients registered at the RSPAL Dr. Skin and Venereology Polyclinic. Ramelan during 2016-2021. The prevalence of Morbus Hansen is dominant in male patients, with a ratio of 5:1 compared to female patients, the avarage age of the groups is 21-30 years and 41-50 years. Based on the type of morbus hansen, 87,5% were Multibacillary (MB) type.